Effects of CreERT2, 4-OH Tamoxifen, and Gender on CFU-F Assays. - Sophie L McHaffie; Nicholas D Hastie; You-Ying Chau (PLoS ONE)
Gene function in stem cell maintenance is often tested by inducing deletion via the Cre-loxP system. However, controls for Cre and other variables are frequently not included. Here we show that when cultured in the presence of 4-OH tamoxifen, bone and marrow cells containing the CreERT2 construct have a reduced colony forming ability. Inactive CreERT2 recombinase, however, has the opposite effect. Young female marrow cells containing the inactive CreERT2 construct grew more colonies than cells lacking the construct altogether. Young female control marrow cells (i.e., negative for CreERT2) also produced significantly greater colony numbers when cultured with 4-OH tamoxifen, compared with the ethanol vehicle control. In conclusion, we report that the use of the Cre-loxP system is inadvisable in combination with CFU-F assays, and that appropriate controls should be in place to extend the future use of Cre-loxP in alternate assays.